Education and Processing Practice of Animal Protein-Based Supplementary Food (PMT) in Kadur Village, Rupat, Bengkalis - Muharni Harahap; Yola Humaroh (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background of study: Nutrition problems among pregnant women and toddlers are key factors in preventing stunting. Animal protein plays a vital role in supporting growth, brain development, and immune function; however, its consumption in rural communities remains low. This community service activity was conducted from October 9– 12, 2025, in Kadur Village, Rupat District, Bengkalis Regency. The program aimed to improve the knowledge and skills of pregnant women and mothers of toddlers in processing local supplementary food (PMT) based on animal protein. Methods: The methods included nutrition education, cooking demonstrations using local ingredients, and interactive discussions. Result: The results showed significant knowledge improvement with 94,7% of 46 respondents scoring between 70-100. Conclusion: This activity has the potential for sustainability through the active role of posyandu cadres in supporting balanced nutrition practices in the community.